Association between physical activity and sleep-disordered breathing in male Japanese workers: a cross-sectional study. (December 2017) - Itoh, Hiroaki; Yokoyama, Kazuhito; Matsukawa, Takehisa; Kitamura, Fumihiko
Abstract Background Whether physical activity reduces the risk of sleep-disordered breathing (SDB) for non-obese people remains unclear. The present cross-sectional study examined the association between physical activity and SDB among non-obese male Japanese workers. Methods All 200 workers in a company in Tokyo, Japan, who drove a motor vehicle as part of their job, were invited to be screened for SDB to prevent traffic accidents. Of these, 195 agreed to participate in this study. The number of apnea and hypopnea episodes occurring during one night was measured using a single-channel airflow monitor to obtain an individual respiratory disturbance index (RDI). SDB was defined as RDI ≥15 apneas/hypopneas/h. Non-obese males (body mass index <30 kg/m2 ) were included in the analysis. Unconditional logistic regression analysis was used to calculate crude and adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for SDB by physical activity level tertile, as measured by the International Physical Activity Questionnaire. Results The prevalence of SDB was 26.9%. The unadjusted analysis showed a significant inverse association between physical activity and SDB: crude ORs for the tertiles of physical activity were 1.00 (low), 1.58 (middle), and 0.27 (high) (95% CI 0.08–0.88;P for trend = 0.007). However, this association was attenuated after adjusting for covariates: Adjusted ORs were 1.00 (low), 1.65 (middle), and 0.41 (high) (95% CI 0.10–1.61;P for trend = 0.11). Conclusions In a cross-sectional study among non-obese male workers in Japan, we found no significant association between physical activity and SDB.